(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2021)
Introduction: Almost 10 million patients suffer from tuberculosis all over the world. Miliary tuberculosis accounts for hardly 1-2 % of total tuberculosis cases but is usually fatal if left untreated. With global epidemic of human immunodeficiency virus (HIV) infection chances of developing tuberculosis disease has also increased. In last few decades MTB has shifted to young adults and elderly who are the most productive members of the society. Fifteen adults were diagnosed to have military tuberculosis during last one year and their data were analysed. Persons living with HIV(PLHIV) accounted for 46% of all cases of military TB. Twelve out of 15 were males. None had meningeal involvement. There was no mortality during hospital stay or follow up till date. High index of suspicion in classical clinical settings and early institution of anti-TB treatment can save lives of patients. Sputum for CBNAAT is very helpful in reaching the diagnosis.